SOME CONSIDERATIONS ON THE PAYMENT ORDER REGULATION - Dan VELICU (Challenges of the Knowledge Society)
The delay of payments, or sometimes even their absence, has particularly negative effects on the activity of a company. Debt recovery is an activity that requires a lot of time, involves costs and causes lack of liquidity. In particular, small and medium-sized companies are deeply affected. They are obliged to resort to bank loans which increases operational costs or to delay payments which can bring them into insolvency. Debt recovery is thus an important goal for the current legislator who should create an encouraging legal framework for the development of businesses. The difference between the rules at national level had negative effects on the commercial relations within the European Union. Therefore, the regulation of this framework was carried out in the last decades at the level of the European Union. The different approaches in the practice of the national courts led to the reform of this legislation. This article aims to analyze the way in which the European regulation was transposed into the Romanian legislation and the possible problems or aspects worthy of being emphasized that appeared during this period.